2016
DOI: 10.1186/s40608-016-0096-2
|View full text |Cite
|
Sign up to set email alerts
|

A single oral dose of a polyglucosamine influences the bioavailability of [9-14C]-Oleic acid in adult female Göttingen minipigs

Abstract: BackgroundWorldwide obesity has nearly doubled since 1980 and is a leading risk for global deaths, profoundly affecting morbidity, mortality, health-care costs, and professional and personal quality of life. Treatment of obesity and its consequences include lifestyle intervention, pharmacotherapy, and bariatric surgery. Polyglucosamines have been proposed as an alternative strategy for treating obesity, by reducing the amount of absorbed fat through interaction with dietary fat through various mechanisms. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This is an important characteristic, since the omental fat is one of the causes of the inflammatory processes that are known to facilitate the tendency towards type II diabetes and cardiovascular diseases. This mechanism of the reduction of fat absorption was also determined experimentally, using the labelled oleic acid as marker [6]. It was clearly shown that oleic acid absorption was reduced by the administration of PG.…”
Section: Introductionmentioning
confidence: 76%
“…This is an important characteristic, since the omental fat is one of the causes of the inflammatory processes that are known to facilitate the tendency towards type II diabetes and cardiovascular diseases. This mechanism of the reduction of fat absorption was also determined experimentally, using the labelled oleic acid as marker [6]. It was clearly shown that oleic acid absorption was reduced by the administration of PG.…”
Section: Introductionmentioning
confidence: 76%
“…PG is a low-MW chitosan used in fixed combinations with ascorbic and tartaric acids. Pharmacologic studies have shown that PG reduces BW and increases the glucose elimination in feces ( 10 ), and the concomitant oral administration of [9- 14 C]oleic acid in mini pigs has been found to lead to a consistent decrease in fecal fat content ( 11 ). Gut bacteria seem to use the fats bound to PG and released in the large intestine as a source of energy, thus helping to restrict caloric intake and reduce steatorrhea ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The standardized PG has been shown in preclinical studies to reduce the absorption of labelled (C14) oleic acid in Göttingen minipigs, to reduce the BW and increase fat excretion in rats and to increase the acetate excretion in rats [16][17][18]. This last aspect is considered important for the satiety, since acetate was shown to stimulate the grehlin secretion inducing hyperphagia and related sequelae [19].…”
Section: Discussionmentioning
confidence: 99%